Black sisterhoods : paradigms and praxis - Jones, Tamara Bertrand; Davis-Maye, Denise; Rahming, Sophia; Andrew, Jill, 1978- (Demeter Press, 2022)
"Sisterhood is oft elusive, if not a misunderstood concept. Despite all the factors that could impede the development, elevation, and maintenance of sistering relationships, Black women continue to acknowledge the value of sisterhoods. Sistering offers a lifeline of support and validation. Holding membership in an empowering woman-centered relationship is a special kind of privilege. The authors in this volume contest any assumption that sisterhood is limited to blood relationships and physical proximity. In this volume, we consider sisterhood simultaneously as paradigm and praxis. We approach Sisterhood as Paradigm and attempt to parse out the nature of Sisterhood as it is understood in Black communities in the United States. We hope to convey an organized set of ideas about “sisterhood" to create sisterhood as a model of interaction or way of being with one another, specifically among Black women. As we consider how sisterhood could be enacted as practice. Using Sisterhood as a framework, we explore Sisterhood as Peer Support, examining how Black women provide support to peers in academic and professional settings. we embark on a provision of applied exemplars of sistering in emerging digital media in Digital Sisterhood."--